Bone Marrow‐Derived Mesenchymal Stem Cells Have Innate Procoagulant Activity and Cause Microvascular Obstruction Following Intracoronary Delivery: Amelioration by Antithrombin Therapy. (4th June 2015) - Gleeson, Birgitta M.; Martin, Kenneth; Ali, Mohammed T.; Kumar, Arun H. S.; Pillai, M. Gopala‐Krishnan; Kumar, Sujith P. G.; O'Sullivan, John F.; Whelan, Derek; Stocca, Alessia; Khider, Wisam; Barry, Frank P.; O'Brien, Timothy; et al.
Abstract: Mesenchymal stem cells (MSCs) are currently under investigation as tools to preserve cardiac structure and function following acute myocardial infarction (AMI). However, concerns have emerged regarding safety of acute intracoronary (IC) MSC delivery. This study aimed to characterize innate prothrombotic activity of MSC and identify means of its mitigation toward safe and efficacious therapeutic IC MSC delivery post‐AMI. Expression of the initiator of the coagulation cascade tissue factor (TF) on MSC was detected and quantified by immunofluorescence, FACS, and immunoblotting. MSC‐derived TF antigen was catalytically active and capable of supporting thrombin generation in vitro. Addition of MSCs to whole citrated blood enhanced platelet thrombus deposition on collagen at arterial shear, an effect abolished by heparin coadministration. In a porcine AMI model, IC infusion of 25 × 10 6 MSC during reperfusion was associated with a decrease in coronary flow reserve but not when coadministered with an antithrombin agent (heparin). Heparin reduced MSC‐associated thrombosis incorporating platelets and VWF within the microvasculature. Heparin‐assisted therapeutic MSC delivery also reduced apoptosis in the infarct border zone at 24 hours, significantly improved infarct size, left ventricular (LV) ejection fraction, LV volumes, wall motion, and attenuated histologic evidence of scar formation at 6 weeks post‐AMI. Heparin alone or heparin‐assisted fibroblast control cell delivery had no such effect. Procoagulant TF activity of therapeutic MSCs is associated with reductions in myocardial perfusion when delivered IC may be successfully managed by heparin coadministration. This study highlights an important mechanistic insight into safety concerns associated with therapeutic IC MSC delivery for AMI. Stem Cells 2015;33:2726–2737